Improved resolution in extracellular vesicle populations using 405 instead of 488 nm side scatter. Issue 1 (22nd March 2018) - McVey, Mark J.; Spring, Christopher M.; Kuebler, Wolfgang M.
ABSTRACT: Improvements in identification and assessment of extracellular vesicles (EVs) have fuelled a recent surge in EV publications investigating their roles as biomarkers and mediators of disease. Meaningful scientific comparisons are, however, hampered by difficulties in accurate, reproducible enumeration and characterization of EVs in biological fluids. High‐sensitivity flow cytometry (FCM) is presently the most commonly applied strategy to assess EVs, yet its utility is limited by variant ability to resolve smaller EVs. Here, we propose the use of 405 nm (violet) wavelength lasers in place of 488 nm (blue) for side scatter (SSC) detection to obtain greater resolution of EVs using high‐sensitivity FCM. To test this hypothesis, we modelled EV resolution by violet versus blue SSC in silico and compared resolution of reference beads and biological EVs from plasma and bronchoalveolar lavage (BAL) fluid using either violet or blue wavelength SSC EV detection. Mie scatter modelling predicted that violet as compared to blue SSC increases resolution of small (100–500 nm) spherical particles with refractive indices (1.34–1.46) similar to EVs by approximately twofold in terms of light intensity and by nearly 20% in SSC signal quantum efficiency. Resolution of reference beads was improved by violet instead of blue SSC with two‐ and fivefold decreases in coefficients of variation for particles of 300–500 nm and 180–240 nm size, respectively. Resolution was similarly improved for detection of EVs from plasma or BAL fluid. Violet SSC detection for high‐sensitivity FCM allows for significantly greater resolution of EVs in plasma and BAL compared to conventional blue SSC and particularly improves resolution of smaller EVs. Notably, the proposed strategy is readily implementable and inexpensive for machines already equipped with 405 nm SSC or the ability to accommodate 405/10 nm bandpass filters in their violet detector arrays.